PENGARUH PENGENDALIAN INTERNAL DAN BUKTI AUDIT TERHADAP OPINI AUDIT (Studi Empiris di Kantor Akuntan Publik di Jakarta Timur) - Ayu Ratna Sari; Herry Winarto (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2020)
The population in this study amounted to 40 KAP in the East Jakarta area. The sample in this study uses Cluster Sampling, with the criteria for respondents submitted to the Director of Public Accountants by IAI. Data obtained by collecting questionnaires directly to respondents as many as 42 and 42 returned questionnaires, as well as 38 questionnaires that can be processed. Internal Control and Audit Evidence have a significant and positive effect on Audit Opinion and simultaneous results indicate that the variable Internal Control and Audit Evidence contribute significantly and positively to Audit Opinion. This can be seen from the results of the coefficient of determination (R2 test) of 67.8%.